Thickness of coating tested nondestructively based on Welch frequency - Qi Lin; Chun-guang Xu; Hong-juan Yan; Shi-yuan Zhou; Liu Yang (2014 IEEE Far East Forum on Nondestructive Evaluation/Testing, 2014)
A method for ultrasonic thickness measurement of coatings by Welch power spectrum is described. The multiple reflections of ultrasonic waves in coating layer lead to a series of maximum energy occurred in the Welch power spectrum which can be implemented to evaluate the thickness of coatings. A great of experiments verified it is effective and feasible to test nondestructively coating thickness on stainless steel and ceramics used as the substrate by the low-frequency immersion focused ultrasonic wave. The relative errors between the evaluated and actual thickness are estimated less than 6%.The results has proven the feasibility of thickness of coating tested nondestructively based on Welch frequency analysis.